Semantic disambiguation in a MT system based on a bilingual dictionary - Krzysztof JASSEM; Agnieszka WAGNER (Archives of Acoustics)
The paper presents an approach to semantic disambiguation in a transfer MT system based on a bilingual dictionary, i.e. the dictionary built from source-target pairs. The approach assumes building a concept ontology for nouns. The ontological concepts are applied as semantic values in lexical rules for verbs, adjectives and prepositions. A set of "semantic accommodation" rules is developed. The set is consulted during the process of semantic disambiguation that follows syntactical parsing. The approach has been applied in a commercial bi-directional Polish-English MT system called Translatica.